MASKULINITAS TOKOH PEREMPUAN DALAM NOVEL CEWEK!!! KARYA ESTI KINASIH - Indah Pachrunisyah; Charlina Charlina; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research speaks about to analyze masculinity female characters in a novel CEWEK!!! by Esti Kinasih. The method used is descreptive with identifying technique. On this research, the author used two techniques, namely technical documentation anddata collection technique with reading novel CEWEK!!! by Esti Kinasih as a source of overall data, marking and underlining each data in accordance withthe characteristics of masculinity, identify, classify and analyze any data included traits of masculinity in the novel CEWEK!!! by Esti Kinasih. This reseacrh data is the data amount to 156, from the research I have found in the novel CEWEK!!! by Esti Kinasih. This research found there are six characteristics of masculinity, which is active, bold, aggressive, selfish, rational and competitive.Key Word : Masculinity, Female Figure, Novel.